Membina Harmoni Global Melalui Filantropi Berbasis Komunitas - Mustafidah, Wiwit; Ekaningsih, Lely Ana Ferawati; Aini, Aula Izatul; Azhar, Indana Almas (Proceedings of Annual Conference for Muslim Scholars, 2025)
Amidst global challenges, local wisdom offers authentic solutions for fostering harmony. This study aims to analyze the impact of the Omplong LAZISNU Program on the formation and strengthening of attitudes of love and tolerance within the community. Qualitative methods were used to collect data through interviews, observation, and documentation. Data analysis utilized an interactive model. The results indicate that the participatory and inclusive nature of the Omplong program can strengthen social bonds (ukhuwah) and foster empathy. Direct involvement in the giving process fosters a sense of ownership and humanity. In terms of tolerance, this program has proven effective in reducing prejudice because aid distribution implements the principle of rahmatan lil 'alamin. The conclusion is that community-based philanthropy is not merely an economic instrument for poverty alleviation but also a powerful social capital for fostering harmony. This model represents local wisdom that contributes to building the foundation of love and tolerant.